1994
DOI: 10.1002/nme.1620371204
|View full text |Cite
|
Sign up to set email alerts
|

On the non‐singular traction‐BIE in elasticity

Abstract: SUMMARYThe work reported herein develops a generalized traction-BIE formulation which involves only weakly singular integrals (in the three-dimensional problem) or totally regular integrals (in the two-dimensional problem). The first step deals with the terms in the Somigliana displacement identity, and then the derivatives of these terms. The only conditions required for the existence of the traction-BIE and the related Somigliana stress identity are weak continuity of the in-plane derivatives of the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 16 publications
0
31
1
Order By: Relevance
“…If unknown functions are approximated by the polynomials or the polynomials multiplied by a weight function (for the tip elements) all the integrals (hypersingular, singular and regular) involved in this equation can be evaluated in a closed form. The expressions to evaluate the integrals involved in (26) are given in Reference 27.…”
Section: Numerical Algorithm and Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If unknown functions are approximated by the polynomials or the polynomials multiplied by a weight function (for the tip elements) all the integrals (hypersingular, singular and regular) involved in this equation can be evaluated in a closed form. The expressions to evaluate the integrals involved in (26) are given in Reference 27.…”
Section: Numerical Algorithm and Numerical Resultsmentioning
confidence: 99%
“…It can be written as (26) where¸is the totality of external and internal boundaries; u"u>!u\ is the displacement discontinuity (DD); u> and u\ are the limit values of the displacements if we approach the contour from its left or right side, respectively; " L #i O ; L is a normal and O is a shear traction on¸; the unit normal n is directed to the right of the direction of travel; the direction of travel is arbitrary for contact boundaries between regions; it is counterclockwise for the external boundary; a bar over a symbol denotes complex conjugation; the origin of the co-ordinate system is assumed to be inside some region; i"(!1;…”
Section: Chsiementioning
confidence: 99%
“…In spite of the very successful numerical results reported by Richardson et al (1997), Richardson and Cruse (1999), Chien et al (1991), Huang and Cruse (1994) using various forms of these relaxed algorithms combined with piece-wise C 1,α interpolations, Martin and Rizzo (1996), Krishnasamy et al (1992) have concluded that these algorithms could not be theoretically justified. This means that, from a strictly mathematical point of view, only boundary element implementations that ensure C 0,α or C 1,α continuity at each collocation point can be applied in the discretizations of the standard, or the hypersingular boundary integral equations, respectively.…”
Section: Paper Accepted April 2009 Technical Editor: Nestor a Zouamentioning
confidence: 96%
“…The next section discusses the discretization of these integral equations, where the boundary is discretized into standard isoparametric elements, which satisfy all the continuity requirements for the potential-BIE, but do not satisfy the continuity requirements for the flux-BIE at a finite number of inter-element nodes in case standard continuous isoparametric boundary elements are used. Since these continuity requirements refer only to collocation points, a 'relaxed continuity' approach is introduced for the case of collocation at an inter-element node according to Huang and Cruse (1994), Cruse and Richardson (1996), Richardson et al (1997), Richardson and Cruse (1999), and different alternatives are discussed, which either allow or avoid the collocation at such nodes. Numerical results obtained from these alternatives, as well as from the self-regular potential BIE are presented.…”
Section: Self-regular Bie For 2-d Potential Problemsmentioning
confidence: 99%
“…For simplicity, let us take x = 0 and define T(y) = T(0, y). Then, we have wheref, is defined by (9).…”
Section: Tangential Derivative Of a Single-layer Potentialmentioning
confidence: 99%